PENGARUH KEPUASAN KERJA TERHADAP KINERJA APARATUR PEMERINTAH DESA DALAM PENGELOLAAN KEUANGAN DESA DI KECAMATAN AIR HANGAT TIMUR KABUPATEN KERINCI - Anuril Awal; Syamsir Syamsir (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
The purpose of this study was to determine the effect of job satisfaction on the performance of village government officials in the management of village finances in the east warm water district in the district of Kerinci. This research is an associative research using quantitative methods. The population in this study is the village government apparatus in the east warm water district of Kerinci Regency. Sampling using simple random sampling technique. Data collection was carried out using a questionnaire with Likert scale measurements and interviews. Data were analyzed using simple linear regression test analysis techniques. Based on the analysis of the coefficient of determination obtained R square figures of 0.352 or 35.2%. This shows that there is a significant effect of job satisfaction on the performance of village government officials in the management of village finances in the warm water district east of Kerinci Regency. Job satisfaction variable contributed to the performance of the village government apparatus in village financial management by 35.2% while the remaining 64.8% was influenced by other variables not examined by researchers.